Qualidade de vida no trabalho de pessoa com deficiência: um estudo de múltiplos casos no setor industrial da cidade de Ponta Grossa - Cazini, Janaina (2013)
The labor market and public policies are part of the stage of social transformation that is shaping the profile management organizations, called of integration of people with disabilities in the production world. Such a move supported by the "Quota Law" - requires organizations that have from 100 employees to hire people with disabilities in a progressive fraction of 2% to 5% - its largest representation is in the industrial sector, at the same time has an environment highly mechanized and technologically innovative. From this scenario, was held out a survey to map the levels of satisfaction of persons with disabilities who are working in the industrial sector of Ponta Grossa city, based on the evaluation criteria for the Quality of Working Life. For both, the instrument used in this research is the questionnaire Quality of Work Life – by Carvalho-Freitas (2007), adapted the determinants established by Walton (1973). Thus, this research is characterized as applied, with goals exploratory in quantitative character – from a multiple cases study - where the analysis tool was applied in three industrials organizations, located in the city of Ponta Grossa – Paraná, of the segments: Food and Wood, all large-sized, with a total of 1693 employees, with a population of 24 employees with disabilities, of which 58% (14) were women and 42% (10) men. The diagnosis showed that employees with disabilities are satisfied with the working conditions, as well as labor rights, work-life balance and relevance of their work. One factor that presents itself as dissonant refers to the lack of opportunities for professional growth and salary in your production environment. Besides these results, one can observe that the architectural and technological structures, are not barriers in the process of their inclusion in the production environment, but the attitudes of people who do not have disabilities, due to lack of awareness and knowledge of the reality of the person with disability, generating stigma that disability raises incompetence at work.